Bronchiolitis and its Different Ways of Management in Raparin Teaching Hospital, Erbil-Iraq - Loqa Hanna , Sasan (Diyala Journal of Medicine, 2023)
Background: Despite the prevalence, global impact, financial burden, and mortality and morbidity related to bronchiolitis, clinical management still seems to be difficult. Objective: To describe the diversity medical treatment options used to manage bronchiolitis and conclude the safest and most effective way to treat it in order to help the development of an evidence based treatment protocol at Raparin teaching hospital. Patients and Methods: This current study design was randomized controlled trial, in which total of 125 children presented with bronchiolitis enrolled in our study, we divided them into five groups (A, B, C, D and E), each of 25 cases. All the groups received supportive treatment in the form of oxygen and intravenous (IV) fluid in addition to specific treatment except group A subjects who received supportive treatment only. The treatments were The study was conducted at the inpatient wards of Raparin teaching hospital in Erbil city-Iraq, from the period of 1st January to 1st August 2022. The infants and children’s age was ranging from 1 to 60 months with clinical diagnosis of bronchiolitis. Results: There was non-significant statistical association between treatment groups and presence of wheeze after treatment (p:0.538), while statistically significant association between various treatment modalities (groups) and cough after treatment (p:0.006) in the same way the association was significant with accessory muscle use after treatment (p:0.037). Conclusion: Generally patients in groups B (inhaled bronchodilator) and D (inhaled bronchodilator and intravenous steroids) had better response rates in terms of cough, accessory muscle use, respiratory rate (tachypnea), time to resolution of fever and coryza, duration of IV fluid therapy, oxygen therapy and hospital stay. Which conclude using of inhaled bronchodilator and IV steroid